Pengukuran Prestasi Kerja Karyawan Menggunakan Motivasi Pada Badan Pengelolaan Keuangan Daerah Kota Metro - Suharto Suharto (Universitas Muhammadiyah Metro, 2017)
The aim of this research is to find the relationship between work motivation and employee performance. This research used survey method. The total population is 86 employees. Based on Slovin method, samples taken by random sampling are as much as 70 respondents. The analytical tool used is Rank Spearman correlation, by using hypothesis testing of distribution Z. Based on the calculation results obtained that the work motivation has a significant relationship with employee performance. It means that the higher the motivation of work, the higher the performance of employees.